2001
DOI: 10.1159/000054902
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Rivastigmine Treatment Reduces EEG Slow-Wave Power in Alzheimer Patients

Abstract: The effects of a 5-day treatment with rivastigmine on the resting EEG power spectrum were studied in 15 mildly to moderately ill Alzheimer patients. In these patients, beta power was positively correlated with cognitive performance and negatively correlated with functional impairment. Rivastigmine produced a decrease in delta and theta power with no effect of hemisphere and electrode position. Delta power decrease reflects the cerebral cholinergic action of rivastigmine and may thus allow a quantitative assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 26 publications
5
34
0
2
Order By: Relevance
“…In this regard, the mechanism explaining the present results might be different from that explaining the shortterm effects of therapy on the EEG rhythms. Indeed, previous studies in AD patients have shown that AChEIs mostly reduce the excess of cortical delta or theta rhythms but did not affect alpha rhythms, at least in the short run (Adler and Brassen, 2001;Adler et al, 2004;Brassen and Adler, 2003). The therapy would restore the typical abnormalities of the EEG rhythmicity around 2 -12 Hz in mild AD patients (Reeves et al, 2002;Brassen and Adler, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, the mechanism explaining the present results might be different from that explaining the shortterm effects of therapy on the EEG rhythms. Indeed, previous studies in AD patients have shown that AChEIs mostly reduce the excess of cortical delta or theta rhythms but did not affect alpha rhythms, at least in the short run (Adler and Brassen, 2001;Adler et al, 2004;Brassen and Adler, 2003). The therapy would restore the typical abnormalities of the EEG rhythmicity around 2 -12 Hz in mild AD patients (Reeves et al, 2002;Brassen and Adler, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…An improvement in classical qEEG parameters was reported after short-term [11], medium-term (e.g., 6 weeks) [12], and even long-term [13] therapy. Very recently, a power reduction in slow frequencies has been observed after 5 days of rivastigmine therapy as well [14]. Concerning donepezil, probably the most widely used AChEI, the only available data show an increased amplitude of hippocampal activity in rats [15] and a decrease in P300 latency by cognitive event-related potentials in AD patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with previous quantitative EEG studies that showed a shift of the power spectral EEG towards 'normalization'. In particular, after short-term (5 days to 2 weeks) rivastigmine treatment, three previous studies showed a decrease of delta (Adler and Brassen 2001) and of theta (Adler and Brassen 2001;Adler et al 2004;Brassen and Adler 2003). To our knowledge, the present paper is the first long-term (3 months) study that used rivastigmine and that reports a stabilization of these electrophysiological effects.…”
Section: Discussionmentioning
confidence: 88%
“…Treatment with ChE-I has been shown to decrease the amount of slow EEG activity, i.e., to 'normalize' the EEG power spectrum (e.g., Adler and Brassen 2001;Balkan et al 2003;Jelic et al 1998;Kogan et al 2001).…”
Section: Introductionmentioning
confidence: 99%